2020
DOI: 10.3390/jcm9092842
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Females with Rett Syndrome and Those with Multi-Comorbid Autism Spectrum Disorder Using Physiological Biomarkers: A Novel Approach

Abstract: This study explored the use of wearable sensor technology to investigate autonomic function in children with autism spectrum disorder (ASD) and Rett syndrome (RTT). We aimed to identify autonomic biomarkers that can correctly differentiate females with ASD and Rett Syndrome using an innovative methodology that applies machine learning approaches. Our findings suggest that we can predict (95%) the status of ASD/Rett. We conclude that physiological biomarkers may be able to assist in the differentiation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Some other potential markers of this Special Issue include the epidermal growth factor (EGF) at the onset of the exacerbation of depressive or hypomanic/manic episodes [33] and neutrophil-to-lymphocyte (NLR) ratio, which has been suggested for differentiating bipolar from unipolar depression [34]. In autism spectrum disorder (ASD), a physiological biomarker collected from a wearable sensor's data was found to be helpful in its differential diagnosis [35], and some augmentations were suggested to help in its treatment [36]. Earlier studies have also suggested that mental symptoms, such as rigidity, stereotypical behaviour that might also be due to the inhibiting properties of the inflammatory state on the brain in persons suffering from autism spectrum disorders, could be connected to inflammation.…”
Section: Other Immune-related Markersmentioning
confidence: 99%
“…Some other potential markers of this Special Issue include the epidermal growth factor (EGF) at the onset of the exacerbation of depressive or hypomanic/manic episodes [33] and neutrophil-to-lymphocyte (NLR) ratio, which has been suggested for differentiating bipolar from unipolar depression [34]. In autism spectrum disorder (ASD), a physiological biomarker collected from a wearable sensor's data was found to be helpful in its differential diagnosis [35], and some augmentations were suggested to help in its treatment [36]. Earlier studies have also suggested that mental symptoms, such as rigidity, stereotypical behaviour that might also be due to the inhibiting properties of the inflammatory state on the brain in persons suffering from autism spectrum disorders, could be connected to inflammation.…”
Section: Other Immune-related Markersmentioning
confidence: 99%
“…Moreover, in a pilot study, we have previously used non-invasive wearable sensors to profile emotional, behavioural and autonomic dysregulation (EBAD) in 10 Rett patients to assess whether biomarkers of HRV and electrodermal activity (EDA) can be used in the management of EBAD in these patients [ 21 ]. Physiological biomarkers measured by wearable sensors can also help to demarcate patients with RTT from those with ASD [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These features being used is consistent with other studies in RTT that explore HRV, temperature, and accelerometer measures. 20 , 39 , 40 , 73 …”
Section: Resultsmentioning
confidence: 99%
“…The existing techniques and data for automated sleep analysis are even less applicable to children with special needs, such as RTT. While other works have shown promise using automated algorithms with physiology and accelerometer data to differentiate between autism 39 and to classify high severity and low severity RTT, 40 to our knowledge, there exist no studies that utilize automated algorithms with physiological and accelerometer data for sleep analysis of children with RTT.…”
Section: Introductionmentioning
confidence: 99%